(untitled) (Journal of Entrepreneurship and Business, 2021)
Academic spin-offs are increasingly assuming a relevant role in the social and economic contexts. However, only a few studies have looked at the specific role of human capital in these organisations. The contradictory dimension in human capital is the role of the founder’s education, in which some studies have revealed the relationship between entrepreneurial motivation and education levels. Other studies indicated that these two variables are uncorrelated. Hence, this study seeks to explore and understand the reasons for these contradictory results by conducting case studies using in-depth interviews on six Portuguese academic spin-offs. The findings have allowed us to understand causes and difficulties experienced by Ph.D. students to create new ventures. Furthermore, they also have allowed us to explore the importance of complementary professional and technical training in entrepreneurial motivations.